Alex Grant and the Big Ditch: Building the Welland Ship Canal - Styran, Roberta; Taylor, Robert (Ontario History, 2017)
The technological history of the building of the Welland ship canal (1913-1932) is well recorded with photographs, documents, maps and plans in various archives. On the other hand, the social history of this saga is harder for the reader to discover because the engineers, contractors, and labourers have left little trace of their experiences “on the ground.” Fortunately, a diary kept by the engineer in charge, Alexander J. Grant, has come to life. Covering the longest period of construction, it chronicles the day-to-day problems of a hard-working, intelligent professional -- but also offers glimpses into the emotional and social life of the man. It will be a valuable source for a future biographer of this remarkable engineer.